2005
DOI: 10.1007/bf03022051
|View full text |Cite
|
Sign up to set email alerts
|

Communication between anesthesiologists, patients and the anesthesia team: a descriptive study of induction and emergence

Abstract: Purpose: Although the importance of communication skills in anesthetic practice is increasingly recognized, formal communication skills training has hitherto dealt only with limited aspects of this professional activity. We aimed to document and analyze the informally-learned communication that takes place between anesthesia personnel and patients at induction of and emergence from general anesthesia. Methods:We adopted an ethnographic approach based principally on observation of anesthesia personnel at work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 14 publications
0
30
0
2
Order By: Relevance
“…27,28 These have been focused largely on doctor-patient relationships, but we are now beginning to develop a better understanding regarding how to communicate effectively with colleagues. 29,30 Techniques such as SBAR (Situation, Background, Assessment, Recommendation) 31 and closed-loop communication 32 This section clearly follows the previous one. Effective communication is key to good team work, but good team work is more than good communication.…”
Section: Communicatormentioning
confidence: 94%
“…27,28 These have been focused largely on doctor-patient relationships, but we are now beginning to develop a better understanding regarding how to communicate effectively with colleagues. 29,30 Techniques such as SBAR (Situation, Background, Assessment, Recommendation) 31 and closed-loop communication 32 This section clearly follows the previous one. Effective communication is key to good team work, but good team work is more than good communication.…”
Section: Communicatormentioning
confidence: 94%
“…1,2 Since evidence for best practices is derived from both quantitative and qualitative sources, 3 it is worthwhile to explore some of the intellectual and methodological foundations of ethnographic studies like Smith et al's paper in this issue, "Communication between anesthesiologists, patients and the anesthesia team: a descriptive study of induction and emergence". 4 I will begin with a discussion of the foundations of ethnographic research, then will highlight specific indicators of quality found in their paper. This introduction is intended to draw attention to a growing body of ethnographies that illuminate expert practice in anesthesia.…”
mentioning
confidence: 99%
“…In their paper, Smith et al 4 argue that the ethnographic approach is ideal for illuminating the tacit knowledge developed by professionals in the practice world, and their study presents some intriguing insights into communication during induction and emergence. The authors have taken an original approach to the issue of communication by seeking to reveal patterns of communication in everyday practice.…”
mentioning
confidence: 99%
See 2 more Smart Citations